Design and development of mechatronics weight loss pill - Chua, Xing Rong. (2013)
This report aims to design a mechatronic weight loss pill that can make one fill satiety by occupying the space in the stomach cavity. It also aims to improve efficacy and reduce discomfort in patients. This will aid patient to reduce food intake and lose weight more effectively. In the report, various methods of weight loss methods have been discussed and compared.